Health Promotion for the Prevention of Extraordinary Events or Outbreaks: A Systematic Review - Katmini, Katmini; Inayatun Nazliyah (Chakra Brahmanda Lentera Institute, 2024)
Background: Health promotion is key in dealing with extraordinary events or outbreaks. This approach empowers the public to understand disease risks, adopt preventive behaviors, and improve compliance with health protocols. Various health promotion interventions have been implemented in recent decades to deal with outbreaks such as dengue fever, influenza, and the COVID-19 pandemic. However, a systematic study is still needed to evaluate the strategies' effectiveness and identify existing challenges and opportunities. This study aims to systematically assess the role of health promotion in managing outbreaks, focusing on best practices, barriers, and opportunities for implementation. Methods: This study uses a systematic review method by following the guidelines of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). Data is obtained from major databases, such as Google Scholar, Science Direct, and PubMed. Article searches were carried out systematically from 2019-2024 using several keywords, namely